Editorial - Hand, Richard J. and Minier, Márta (Journal of Adaptation in Film & Performance, 2016)
Abstract
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qYWZwLjkuMi4xMjdfMg